Mg-Co-based soluble magnesium alloy containing rare earth elements and preparation method of Mg-Co-based soluble magnesium alloy
By adding Co elements and two rare earth elements to the soluble magnesium alloy, a new long-term phase is formed, which solves the shortcomings in strength and dissolution rate of the existing alloys, and achieves efficient dissolution performance and good mechanical properties.
Patent Information
- Application Number
- CN202411177440.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The existing soluble magnesium alloys have shortcomings in strength and dissolution rate, which cannot meet the efficient dissolution needs of fracturing tools in high-temperature aqueous solutions.
A Mg-Co-based soluble magnesium alloy containing rare earth elements was developed. By adding Co elements and two rare earth elements, a new long-term (LPSO) phase was formed to improve the strength and dissolution rate of the alloy.
The dissolution rate and mechanical properties of the alloy are significantly improved, the yield strength and tensile strength reach 240 MPa or above, the elongation is greater than 10%, and the dissolution rate in 3% KCl aqueous solution at 93°C is greater than 80 mg/(cm2·h).
Smart Images

Figure CN119530623A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nonferrous metals, and in particular to a Mg-Co based soluble magnesium alloy containing rare earth elements and a preparation method and application field thereof. Background Art
[0002] my country's shale gas and shale oil reserves are among the highest in the world, and the future development prospects are broad. The current mainstream horizontal well mining commonly uses staged fracturing technology, and a key component of this technology is the fracturing tool, including temporary plugging balls, ball seats, and bridge plugs. At present, the commonly used fracturing tools are made of soluble magnesium alloys, which can dissolve by themselves in the later stage of service, thereby improving construction efficiency. Pure magnesium has poor mechanical properties and the dissolution rate is lower than the required speed, so it is necessary to develop new soluble magnesium alloys.
[0003] Patent document 1 (CN118256784A) discloses a soluble magnesium alloy, characterized in that the magnesium alloy is composed of 0.05% to 3% Mn, 0.05% to 1% Ni, 0.05% to 1% X and the balance Mg by mass percentage; wherein X is one or more of Cu, Fe, Gd and Y; wherein the Mg-Mn-Ni series alloy can achieve the highest performance in the cast state: yield strength 155 MPa, tensile strength 210 MPa, elongation 31%, and dissolution rate in 3% KCl aqueous solution at 93°C is 50 mg / (cm 2 h). This alloy series has lower strength and intermediate dissolution rate.
[0004] Patent document 2 (CN113025857A) discloses a soluble magnesium alloy, which includes Li and M elements, and the mass percentage of each element is: Li: 8.0-14.0 wt.%; M is at least one of Ni and Cu elements, wherein Ni: 0.01-5.0 wt.%, Cu: 0.01-5.0 wt.%, and the balance is Mg; the alloy series has low mechanical properties, with a maximum yield strength of 119.5 MPa and a maximum tensile strength of 147 MPa. The dissolution rate in a 3% KCl aqueous solution at 93°C is up to 70 mg / (cm 2 h). The dissolution rate of this alloy series is already able to meet the application requirements, but the strength is still low.
[0005] Patent document 3 (CN110863130A) discloses a soluble magnesium alloy, wherein the soluble magnesium alloy is composed of Mg-Al-Zn-Mn-Ca-Ni-Ag-X, wherein X represents a combination of one or more elements of Cu, Fe, Zr, Sn, Gd, Y, Nd, Ce, Sr, and Er; wherein the extruded Mg-6Al-1.2Zn-0.1Mn-0.3Ca-0.25Ni-0.3Ag-0.1Sn alloy has a room temperature tensile strength of 325 MPa, a yield strength of 213 MPa, and an elongation of 16.3%. At 93°C, the corrosion rate in a 3% KCl solution is about 56 mg / (cm 2 h). The mechanical properties of this alloy series are good, but the dissolution rate still does not meet the requirements. Summary of the invention
[0006] The object of the present invention is to provide a Mg-Co based soluble magnesium alloy containing rare earth elements and a preparation method thereof. To achieve the above object, the present invention provides
[0007] A Mg-Co based soluble magnesium alloy containing rare earth elements, characterized in that the soluble magnesium alloy consists of the following components in terms of mass percentage: Mg-Co-RE 1 -RE 2 , of which the Co content is 0.5% to 10%; rare earth element RE 1 With RE 2 Specifically, any two of Sc, La, Sm, Pr, Pm, Eu, Tb, Dy, Ho, Tm, Lu, Gd, Y, Nd, Er, Yb, and Ce, 0.01 wt.% <RE 1 < 20 wt.%, 0.01 wt.%< RE 2 < 20 wt.%, the balance is Mg; the soluble magnesium alloy contains a new long period phase (LPSO) phase, the composition of which is (Mg, Co)(RE 1 , R.E. 2 ), the width range is 10 to 50 μm, the average spacing is 10 to 40 μm, and the volume fraction accounts for 20 to 40%. This LPSO phase plays a role in increasing the dissolution rate of the alloy and improving the strength and hardness of the alloy; the dissolution rate of the soluble magnesium alloy in an aqueous solution containing 3% KCl at 93°C is greater than 80 mg / (cm 2 h).
[0008] The method for preparing the soluble magnesium alloy as described above is characterized in that the specific preparation steps are as follows:
[0009] S1 Ratio of raw materials: pure Mg ingot, pure Co powder with spherical particle size less than 50 μm, Mg-30RE 1and Mg-30RE 2 The intermediate alloy is used as the raw material, and the raw material ratio is determined according to the content of alloy elements;
[0010] S2 casting: firstly, pure Mg ingots and Mg-30RE are melted in the furnace. 1 and Mg-30RE 2 The intermediate alloy is melted at 750°C and kept at this temperature for 2 to 4 minutes, then pure Co powder is added, and the furnace temperature is raised to 850°C and kept at this temperature for 1 to 6 minutes, with electromagnetic stirring to make the three alloy elements evenly mixed in the alloy melt, especially to make the Co powder fully dissolved; then the alloy melt is poured into a graphite mold and cooled to room temperature to obtain the magnesium alloy ingot of the invention example;
[0011] Furthermore, the magnesium alloy ingot can be subjected to extrusion deformation and aging heat treatment;
[0012] S3 solution treatment: the magnesium alloy ingot is kept at 450° C. to 500° C. for 12 to 24 hours, and then water quenched;
[0013] S4 extrusion: the ingot treated in step S3 is kept at 400°C to 550°C for 0.5 to 2 h, and then extruded to obtain a magnesium alloy rod, the extrusion speed is 0.5 to 2 mm / s, and the extrusion ratio is 16 to 36;
[0014] S5 aging treatment: the rod obtained in step S4 is kept at 150°C to 250°C for 12 to 72 hours. During this process, a precipitate phase dispersed in the Mg matrix is formed. The size of the precipitate phase is less than 100 nm, which can significantly improve the strength of the rod. The average grain size after extrusion is 3 to 6 μm.
[0015] Furthermore, the cast magnesium alloy obtained from S2 has a yield strength greater than 120 MPa, a tensile strength greater than 210 MPa, an elongation greater than 8%, and a hardness greater than 80 HV; and a dissolution rate greater than 80 mg / (cm 2 h).
[0016] Furthermore, the aged magnesium alloy obtained from S5 has a yield strength greater than 240 MPa, a tensile strength greater than 330 MPa, an elongation greater than 10%, and a hardness greater than 100 HV; and a dissolution rate greater than 80 mg / (cm 2 h).
[0017] The characteristic of step S1 of the present invention is that since the melting point of Co is as high as 1495°C, the present invention selects Co powder with a spherical particle size of less than 50 μm through experimental research, and under the process parameters of the subsequent step S2, the uniform distribution of the Co element in the invention alloy melt can be achieved.
[0018] In contrast, existing Co-containing magnesium alloys are usually smelted with Mg-Co master alloys. For example, the literature (WANG Z, CAO H, ZHENG H, et al. Effect of aging treatment on the mechanical propertyand precipitation transformation of Mg–Co–Y alloy [J]. Materials Science and Engineering: A, 881, 2023, 145322.) uses Mg-10Co (wt.%) master alloy.
[0019] The characteristics of S2 casting are: the microstructure of the magnesium alloy ingot obtained by pouring it into a graphite mold and cooling it to room temperature is composed of (Mg, Co)(RE 1 , R.E. 2 ) is a new long period structure (LPSO) phase. Compared with the reported LPSO phase, this LPSO phase is characterized by containing Co and two rare earth elements at the same time; compared with similar rare earth soluble magnesium alloys without Co, the dissolution rate is 3 times or more than that of Mg–10Gd–3Y–0.2Zr–0.8Ni.
[0020] The room temperature tensile mechanical properties of the cast magnesium alloy obtained in this step are as follows: yield strength greater than 120 MPa, tensile strength greater than 210 MPa, elongation greater than 8%, hardness greater than 80 HV; its dissolution rate in an aqueous solution containing 3% KCl at 93°C is greater than 80 mg / (cm 2 h).
[0021] Furthermore, the magnesium alloy ingot can be subjected to extrusion deformation and aging heat treatment.
[0022] S5 aging treatment: The rod obtained in step S4 is kept at 150℃~250℃ for 12~72h.
[0023] The room temperature tensile mechanical properties of the aged magnesium alloy obtained in this step are as follows: yield strength greater than 240 MPa, tensile strength greater than 330 MPa, elongation greater than 10%, hardness greater than 100 HV; in an aqueous solution containing 3% KCl at 93°C, the dissolution rate is greater than 80 mg / (cm 2 h).
[0024] The soluble magnesium alloy of the present invention has the following characteristics and advantages:
[0025] (1) The soluble magnesium alloy of the present invention contains a new LPSO phase (Mg, Co) (RE 1 , R.E. 2 ), the width of the layered LPSO phase ranges from 10 to 50 μm, the average spacing is 10 to 40 μm, and the volume fraction accounts for 20 to 40%. , which can simultaneously improve strength and dissolution rate;
[0026] (2) The dissolution rate of the soluble magnesium alloy of the present invention in a 93°C aqueous solution containing 3% KCl is greater than 80 mg / (cm 2 h), the dissolution rate is more than three times that of the Mg–10Gd–3Y–0.2Zr–0.8Ni alloy compared with alloys containing similar rare earth elements but without Co;
[0027] (3) The soluble magnesium alloy of the present invention has good comprehensive performance, and the dissolution rate of the extruded alloy is maintained at 80 mg / (cm 2 h) and above, the tensile strength reaches up to 390 MPa and the elongation is greater than 10%. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the new LPSO phase contained in the alloy of Invention Example 1 in Example 1. DETAILED DESCRIPTION
[0029] In order to make the technical solution of the present invention more clear, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, and can be implemented by appropriate changes without changing the gist.
[0030] Embodiment 1:
[0031] It should be noted that RE 1 With RE 2 Any two of Sc, La, Sm, Pr, Pm, Eu, Tb, Dy, Ho, Tm, Lu, Gd, Y, Nd, Er, Yb, and Ce are not limited to the following combinations. Some examples are now selected to further explain the preparation and processing methods of the alloy of the present invention and its properties. The alloy composition ratio is expressed in mass fraction as shown in Table 1-1.
[0032] Table 1-1
[0033]
[0034] The casting process of all the inventive magnesium alloys in Table 1-1 is as follows: pure Mg ingot, pure Co powder with a spherical particle size of less than 50 μm, Mg-30RE 1 and Mg-30RE2 The intermediate alloy is used as the raw material, and the raw material ratio is determined according to the content of the alloy elements. First, pure Mg ingots and Mg-30RE are melted in a furnace. 1 and Mg-30RE 2 The intermediate alloy is melted at 750°C and kept warm for 2 to 4 minutes, then pure Co powder is added, and the furnace temperature is raised to 850°C and kept warm for 1 to 6 minutes, with electromagnetic stirring to allow the three alloy elements to be evenly mixed in the alloy melt, especially to allow the Co powder to be fully dissolved; the alloy melt is then poured into a graphite mold and cooled to room temperature to obtain an inventive magnesium alloy ingot.
[0035] The microstructure of the alloy of Example 1 was observed by scanning electron microscopy (SEM). Figure 1 As shown. The average width of the layered LPSO phase is 30 μm, the average spacing is 40 μm, and the volume fraction is 30%. Through the energy spectrometer analysis in the scanning electron microscope, it was found that the LPSO phase contains Co and two rare earth elements. Figure 1 The specific composition results of element contents (at.%) at different positions are shown in Table 1-2.
[0036] Table 1-2
[0037]
[0038] Embodiment 2:
[0039] The room temperature tensile mechanical properties of the inventive alloy obtained in Example 1 were evaluated according to the national standard GB / T228.1-2010 "Metallic material tensile test Part 1: Room temperature test method"; according to the national standard GB / T19746-2018 "Corrosion salt solution immersion test for metals and alloys" and GB / T16545-2015 "Removal of corrosion products on corrosion specimens of metals and alloys", the dissolution rate was tested at 93°C using an aqueous solution containing 3wt.% KCl; the obtained properties are shown in Table 2-1. Among them, the highest dissolution rate of inventive example 1 is 95 mg / (cm 2 h); Inventive Example 18 has the best comprehensive performance, with an elongation of 14.4%, and can be used for larger deformation processing.
[0040] Table 2-1
[0041]
[0042] Embodiment 3:
[0043] The alloy ingot obtained in Example 1 was subsequently processed as follows:
[0044] (1) Solution treatment: The magnesium alloy ingot of the invention example is kept at 450°C to 500°C for 12 to 24 hours (h represents hours hereafter), and then water quenched. The specific process parameters are shown in Table 3-1;
[0045] (2) Extrusion: The solution treated alloy ingot is kept at 400°C to 550°C for 0.5 to 2 h, and then extruded to obtain a rod. The extrusion speed is 0.5 to 2 mm / s, and the extrusion ratio is 16 to 36. The specific process parameters are shown in Table 3-1.
[0046] (3) Aging treatment: The extruded rod is kept at 150℃~250℃ for 12~72 h. The specific corresponding aging temperature and time are shown in Table 3-1. In this process, a precipitate phase dispersed in the Mg matrix is formed. The size of the precipitate phase is less than 100 nm, which can significantly improve the strength of the rod.
[0047] Table 3-1
[0048]
[0049] Embodiment 4:
[0050] The mechanical properties and dissolution rate of the aged alloy obtained in Example 3 were tested according to the method in Example 2, and the obtained properties are shown in Table 4-1. The yield strength of all alloys is greater than 240 MPa, the tensile strength is greater than 330 MPa, the elongation is greater than 10%, and the hardness is greater than 100 HV; in an aqueous solution containing 3% KCl at 93°C, the dissolution rate is greater than 80 mg / (cm 2 ·h). Example 3 has the highest elongation, reaching 19.8%, and its dissolution rate reaches 93 mg / (cm 2 h).
[0051] Table 4-1
[0052]
[0053] Comparative Example 1:
[0054] The alloy composition is Mg-9.8Gd-2.8Y-0.5Zr, and the raw materials are selected in proportion according to the content of the alloy elements. Then the raw materials are added together into a vacuum melting furnace, heated to 750°C, kept warm and refined for 5 to 10 minutes, and electromagnetic stirring is performed to make the alloy elements evenly mixed, and then poured into a graphite mold and cooled to room temperature to obtain a magnesium alloy ingot.
[0055] The properties of the cast alloy obtained in Comparative Example 1 measured according to the test method in Example 2 are as follows: yield strength 164 MPa, tensile strength 220 MPa, elongation 2%, hardness 78 HV, dissolution rate 1.5 mg / (cm 2 ·h). The tensile strength of Example 10 in Example 2 (see Table 2-1) is 247 MPa, the elongation is 8.4%, the hardness is 89 HV, and the dissolution rate is 90 mg / (cm 2 ·h). The elongation of all the inventive examples in Example 2 in the cast state is greater than 8%, which is more than 4 times that of the comparative example 1; the dissolution rate of all the inventive examples in Example 2 is greater than 80 mg / (cm 2 h), which is more than 50 times that of Comparative Example 1.
[0056] Comparative Example 2:
[0057] The alloy composition is Mg-12Gd-3.5Y-3.8Ni-0.05La-1.2Eu-0.5Yb, and the raw materials are selected in proportion according to the content of the alloy elements. Then the raw materials are added together into a vacuum melting furnace, heated to 750°C, kept warm and refined for 5 to 10 minutes, and electromagnetic stirring is performed to mix the alloy elements uniformly, and then poured into a graphite mold and cooled to room temperature to obtain a magnesium alloy ingot.
[0058] The properties of the alloy obtained in Comparative Example 2 measured according to the test method in Example 2 are as follows: yield strength 99 MPa, tensile strength 150 MPa, elongation 3.5%, hardness 75 HV, dissolution rate 44.6 mg / (cm 2 The lowest performance of the cast alloy in the present invention is that of Example 3, with a yield strength of 121 MPa, a tensile strength of 213 MPa, an elongation of 12.8%, a hardness of 85 HV, and a dissolution rate of 90 mg / (cm 2 h). Therefore, the performance of all the inventive examples is better than that of the comparative example 2.
[0059] Comparative Example 3:
[0060] The alloy composition is Mg-14Gd-4.2Y-0.1Ni-1.1Zr-1Eu-1.6Yb, and the raw materials are selected in proportion according to the content of the alloy elements. Then the raw materials are added together into a vacuum melting furnace, heated to 750°C, kept warm and refined for 5 to 10 minutes, and electromagnetic stirring is performed to make the alloy elements evenly mixed, and then poured into a graphite mold and cooled to room temperature to obtain a magnesium alloy ingot.
[0061] The properties of the alloy obtained in Comparative Example 3 measured according to the test method in Example 2 are as follows: yield strength 168 MPa, tensile strength 215 MPa, elongation 0.9%, hardness 80 HV, dissolution rate 1.1 mg / (cm 2 ·h). The tensile strength of the cast alloy in the present invention is 215 MPa, the elongation is 13.0%, the hardness is 87 HV, and the dissolution rate is 90 mg / (cm 2 ·h). The elongation of all the inventive examples is greater than 10%, which is more than 10 times that of comparative example 3; the dissolution rate of all the inventive examples is greater than 80 mg / (cm 2 h), which is more than 70 times that of Comparative Example 3.
[0062] Comparative Example 4:
[0063] The alloy composition is Mg-9.5Gd-2.7Y-0.9Zn-0.8Cu-0.4Ni, and the raw materials are selected in proportion according to the content of alloy elements. Then the raw materials are added together into a vacuum melting furnace, heated to 750°C, kept warm and refined for 5 to 10 minutes, and electromagnetic stirring is performed to mix the alloy elements evenly, and then poured into a graphite mold and cooled to room temperature to obtain a magnesium alloy ingot. The obtained magnesium alloy ingot is homogenized at 470°C for 24 hours, homogenized at 520°C for 24 hours, and then air-cooled. Extrusion is performed at 450°C, with an extrusion ratio of 8:1 and a speed of 0.5 mm / s.
[0064] The properties of the alloy obtained in Comparative Example 4 measured according to the test method in Example 2 are as follows: yield strength 316 MPa, tensile strength 382 MPa, elongation 7%, hardness 92 HV, dissolution rate 46.9 mg / (cm 2 ·h). The highest tensile strength in Table 4-1 is Example 16, which has a tensile strength of 379 MPa; elongation is 10.4%, an increase of 48.6%; hardness is 124 HV, an increase of 34.6%; dissolution rate is 89 mg / (cm 2 h), an increase of 47.3%.
Claims
1. A Mg-Co based soluble magnesium alloy containing rare earth elements, characterized in that: The soluble magnesium alloy is composed of the following components in terms of mass percentage: Mg-Co-RE1-RE2, wherein the Co content is 0.5% to 10%; the rare earth elements RE1 and RE2 are specifically any two of Sc, La, Sm, Pr, Pm, Eu, Tb, Dy, Ho, Tm, Lu, Gd, Y, Nd, Er, Yb, and Ce, 0.01wt.% < RE1 < 20 wt.%, 0.01wt.% < RE2 < 20 wt.%, and the balance is Mg; the soluble magnesium alloy contains a new type of long period (LPSO) phase, which is composed of (Mg, Co)(RE1, RE2), with a width range of 10 to 50 μm, an average spacing of 10 to 40 μm, and a volume fraction of 20 to 40%, and the LPSO phase plays a role in increasing the dissolution rate of the alloy and improving the strength and hardness of the alloy; the dissolution rate of the soluble magnesium alloy in an aqueous solution containing 3% KCl at 93° C. is greater than 80 mg / (cm 2 h).
2. The method for preparing a soluble magnesium alloy according to claim 1, characterized in that: The specific preparation steps are as follows: S1 Proportion of raw materials: Pure Mg ingot, pure Co powder with spherical particle size less than 50 μm, Mg-30RE1 and Mg-30RE2 master alloys are used as raw materials, and the raw materials are proportioned according to the content of alloy elements; S2 casting: first, pure Mg ingot, Mg-30RE1 and Mg-30RE2 master alloys are melted at 750°C in a smelting furnace and kept warm for 2 to 4 minutes, then pure Co powder is added, and the furnace temperature is raised to 850°C and kept warm for 1 to 6 minutes, and electromagnetic stirring is performed to make the three alloy elements evenly mixed in the alloy melt, especially to make the Co powder fully dissolved; then the alloy melt is poured into a graphite mold and cooled to room temperature to obtain the magnesium alloy ingot of the invention example; Furthermore, the magnesium alloy ingot can be subjected to extrusion deformation and aging heat treatment; S3 solution treatment: the magnesium alloy ingot is kept at 450° C. to 500° C. for 12 to 24 hours, and then water quenched; S4 extrusion: the ingot treated in step S3 is kept at 400°C to 550°C for 0.5 to 2 h, and then extruded to obtain a magnesium alloy rod, the extrusion speed is 0.5 to 2 mm / s, and the extrusion ratio is 16 to 36; S5 aging treatment: The rod obtained in step S4 is kept at 150°C to 250°C for 12 to 72 h. During this process, a precipitate phase dispersed in the Mg matrix is formed. The size of the precipitate phase is less than 100 nm, which can significantly improve the strength of the rod. The average grain size after extrusion is 3 to 6 μm.
3. The method for preparing a soluble magnesium alloy according to claim 2, characterized in that: The cast magnesium alloy obtained from S2 has a yield strength greater than 120 MPa, a tensile strength greater than 210 MPa, an elongation greater than 8%, and a hardness greater than 80 HV; its dissolution rate in an aqueous solution containing 3% KCl at 93°C is greater than 80 mg / (cm 2 h).
4. The method for preparing a soluble magnesium alloy according to claim 2, characterized in that: The aged magnesium alloy obtained from S5 has a yield strength greater than 240 MPa, a tensile strength greater than 330 MPa, an elongation greater than 10%, and a hardness greater than 100 HV; in an aqueous solution containing 3% KCl at 93°C, the dissolution rate is greater than 80 mg / (cm 2 h).
Citation Information
Patent Citations
Soluble magnesium alloy and preparation method thereof
CN116949330A
High-strength soluble magnesium alloy and preparation method thereof
CN117660819A
Magnesium alloy having excellent corrosion resistance and wear resistance, and its production method
JP2005068516A
Plastic deformation magnesium alloy having excellent thermal conductivity and flame retardancy, and preparation method
US20180030578A1
Heat-resistant and soluble magnesium alloy, preparation method and use thereof
US20200370156A1